Complexity seems to open a way towards a new Aristotelian-thomistic ontology - Sturmia, Alberto (Acta Biomedica Atenei Parmensis, 2007)
Today’s sciences seem to converge all towards very similar foundational questions. Such claims, both of epistemological and ontological nature, seem to rediscover, in a new fashion some of the most relevant topics of ancient Greek and Mediaeval philosophy of nature, logic and metaphysics, such as the problem of the relationship between the whole and its parts (non redictionism), the problems of the paradoxes arising from the attempt to conceive the entity like an univocal concept (analogy and analogia entis), the problem of the mind-body relationship and that of an adequate cognitive theory (abstraction and immaterial nature of the mind), the complexity of some physical, chemical and biological systems and global properties arising from information (matter-form theory), etc. Medicine too is involved in some of such relevant questions and cannot avoid to take them into a special account.